Extracellular vesicles from periodontal pathogens regulate hepatic steatosis via Toll‐like receptor 2 and plasminogen activator inhibitor‐1 - Kim, Hyun Young; Lim, Younggap; Jang, Ji Sun; Ko, Yeon Kyeong; Choi, Youngnim; Kim, Hong‐Hee; Choi, Bong‐Kyu (Journal of extracellular vesicles, 2024)
Plasminogen activator inhibitor‐1 (PAI‐1) is associated with nonalcoholic fatty liver disease (NAFLD) by lipid accumulation in the liver. In this study, we showed that extracellular vesicles (EVs) from the periodontal pathogens Filifactor alocis and Porphyromonas gingivalis induced steatosis by inducing PAI‐1 in the liver and serum of mice fed a low‐fat diet. PAI‐1 induction was not observed in TLR2−/− mice. When tested using HEK‐Blue hTLR2 cells, human TLR2 reporter cells, the TLR2‐activating ability of serum from NAFLD patients (n = 100) was significantly higher than that of serum from healthy subjects (n = 100). Correlation analysis confirmed that PAI‐1 levels were positively correlated with the TLR2‐activating ability of serum from NAFLD patients and healthy subjects. Amphiphilic molecules in EVs were involved in PAI‐1 induction. Our data demonstrate that the TLR2/PAI‐1 axis is important for hepatic steatosis by EVs of periodontal pathogens.